Compiling high-level languages to DSPs automating the implementation path. - Allen, R. (IEEE Signal processing magazine)
A large and growing number of digital signal processor (DSP) applications are initially prototyped in Matlab, a high-level language that provides concise, intuitive statement of mathematical computations. Work in this elegant language stops at the prototyping stage due to the absence of an effective automatic path to implementation. This articles overviews a set of techniques for automating an implementation path from Matlab to DSPs and provides preliminary results on the effectiveness of such techniques.